Tissue Morphology and Antigenicity in Mouse and Rat Tibia: Comparing 12 Different Decalcification Conditions. (August 2019) - Bogoevski, Kristofor; Woloszyk, Anna; Blackwood, Keith; Woodruff, Maria A.; Glatt, Vaida
Conventional bone decalcification is a time-consuming process and is therefore unsuitable for clinical applications and time-limited research projects. Consequently, we compared the effect of four different decalcification solutions applied at three different temperatures, and assessed the rate of decalcification and the implications on tissue morphology and antigenicity of mouse and rat tibiae. Bones were decalcified with 10% ethylenediaminetetraacetic acid (EDTA), 10% formic acid, 5% hydrochloric acid, and 5% nitric acid at 4C, 25C, and 37C. Decalcification in both species was fastest in nitric acid at 37C and slowest in EDTA at 4C. Histological and immunohistochemical staining confirmed that the conventional protocols of EDTA at 4C and 25C remain the best option regarding the quality of tissue preservation. Whereas formic acid at 4C is a good alternative saving about 90% of the decalcification time, hydrochloric and nitric acids should be avoided particularly in case of rat tibia. By contrast, due to their smaller size, mouse tibiae had shorter decalcification times and tolerated higher temperatures and exposure to acids much better. In conclusion, this study demonstrated that depending on the specific research question and sample size, alternative decalcification methods could be used to decrease the time of decalcification while maintaining histological accuracy.